Household survey analysis of the impact of comprehensive strategies to improve the expanded programme on immunisation at the county level in western China, 2006–2010 - Zhou, Yuqing (BMJ Open, 2016)
OBJECTIVE: To evaluate interventions to improve routine vaccination coverage and caregiver knowledge in China's remote west, where routine immunisation is relatively weak. DESIGN: Prospective pre–post (2006–2010) evaluation in project counties; retrospective comparison based on 2004 administrative data at baseline and surveyed post-intervention (2010) data in selected non-project counties. SETTING: Four project counties and one non-project county in each of four provinces. PARTICIPANTS: 3390 children in project counties at baseline, and 3299 in project and 830 in non-project counties post-intervention; and 3279 caregivers at baseline, and 3389 in project and 830 in non-project counties post-intervention. INTERVENTION: Multicomponent inexpensive knowledge-strengthening and service-strengthening and innovative, multisectoral engagement. DATA COLLECTION: Standard 30-cluster household surveys of vaccine coverage and caregiver interviews pre-intervention and post-intervention in each project county. Similar surveys in one non-project county selected by local authorities in each province post-intervention. Administrative data on vaccination coverage in non-project counties at baseline. PRIMARY OUTCOME MEASURES: Changes in vaccine coverage between baseline and project completion (2010); comparative caregiver knowledge in all counties in 2010. ANALYSIS: Crude (χ(2)) analysis of changes and differences in vaccination coverage and related knowledge. Multiple logistic regression to assess associations with timely coverage. RESULTS: Timely coverage of four routine vaccines increased by 21% (p<0.001) and hepatitis B (HepB) birth dose by 35% (p<0.001) over baseline in project counties. Comparison with non-project counties revealed secular improvement in most provinces, except new vaccine coverage was mostly higher in project counties. Ethnicity, province, birthplace, vaccination site, dual-parental out-migration and parental knowledge had significant associations with coverage. Knowledge increased for all variables but one in project counties (highest p<0.05) and was substantially higher than in non-project counties (p<0.01). CONCLUSIONS: Comprehensive but inexpensive strategies improved vaccination coverage and caretaker knowledge in western China. Establishing multisectoral leadership, involving the education sector and including immunisation in public-sector performance standards, are affordable and effective interventions.